Правове забезпечення протидії домашньому насильству: становлення та розвиток - Гром, Н. О.; Hrom, N. O. (Юридичний бюлетень. - 2024. - Вип. 32. - С. 31-38, 2024)
У статті проаналізовано становлення та розвиток правового забезпечення протидії домашньому насильству, на підставі чого автором запропоновано власне бачення періодизації вказаного процесу.

The article analyzes the formation and development of legal protection against domestic violence, on the basis of which the author proposed his own vision of the periodization of the specified process. The first period falls on the XI–XVI centuries, is characterized by a considerable length of time, and entered history primarily with the codified collection of legal norms of the Ukrainian people "Ruska Pravda", which protected the position of a woman, wife and mother at the legal level: the murder of a woman was punishable by the following the same responsibility as for the murder of a husband. The second period (IX century) is primarily associated with two laws: the AustroHungarian Civil Code, which not only attempted to normalize relations between spouses, parents and children, guardians and orphans, but also established the legal definition of the term seven 'I. The third period (13th – early 20th centuries) was marked by the emergence of two interdependent trends in the protection of human rights and the protection of women's rights, which resulted in the emergence of suffragism (which spread throughout Europe, the United States of America and reached the Ukrainian lands) and were reflected in revolutionary events 1917, which were the beginning of attempts to equalize women in all spheres of social life. The fourth period (the middle and end of the 20th century) without exaggeration became the most saturated and effective in the world in the field of combating domestic violence, when in: 1948 the Universal Declaration of Human Rights was adopted, which proclaimed the equality of men and women, laid the fundamental foundations for the defense of rights women; In 1979, the Convention on the Elimination of All Forms of Discrimination against Women condemned any manifestation of restrictions on this category in all social spheres. The fifth period (the end of the XX–XXI centuries) of independent Ukraine, which as an independent state took a new course, recognizing domestic violence not just as a global problem, but also as a destructive phenomenon that requires complex countermeasures, as well as the development of a legal framework in this area.

В статье проанализировано становление и развитие правового обеспечения противодействия домашнему насилию, на основании чего автором предложено собственное видение периодизации указанного процесса.
Legal security against domestic violence: establishment and development
Keywords: домашнє насильство, періодизація.; історико-правовий аналіз; правове забезпечення; кримінальна відповідальність; адміністративна відповідальність; періодизація; протидія домашньому насильству; domestic violence; historical and legal analysis; legal support; criminal responsibility; administrative responsibility; periodization; combating domestic violence; домашнее насилие; историко-правовой анализ; правовое обеспечение; уголовная ответственность; административная ответственность; периодизация; противодействие домашнему насилию